Factors associated with secondhand tobacco smoke in the home: an exploratory cross-sectional study among women in Aleta Wondo, Ethiopia - Anne Berit Petersen; Lisa M. Thompson; Gezahegn Bekele Dadi; Alemu Tolcha; Janine K. Cataldo (BMC, 2016)
Abstract Background In Ethiopia, female smoking rates are currently low (1 %). However, because of male smoking rates (overall 7.7 % and up to 27 % depending on region), women and children's risk of second hand smoke (SHS) exposure is a pressing concern. In order to develop effective public health interventions that prevent the uptake and exposure to smoking, thereby averting the projected increase in tobacco-induced disease, an understanding of Ethiopian women's practices regarding tobacco is needed. The purpose of this study was to explore Ethiopian women's tobacco use and prevalence of SHS exposure, and to identify covariates associated with SHS exposure. Methods We conducted an exploratory cross-sectional study in Southern Ethiopia between August and October 2014, and systematically sampled households in Aleta Wondo town and surrounding districts. Trained interviewers verbally administered surveys to women 18-55 years of age. Descriptive statistics and multiple logistic regression analyses were performed. Results None of the 353 participants reported current tobacco use and less than 1 % reported ever use, however, 11 % reported ever use of the stimulant leaf khat. Twenty-seven women (7.6 %) reported living with a tobacco user, however, twice that number (14.4 %) overall, and 22 % of urban participants reported that smoking occurred daily in their home. When controlling for other factors, living with a tobacco user (OR = 9.91, 95 % CI [3.32, 29.59]), allowing smoking in the home (OR = 5.67, 95 % CI [2.51, 12.79]), place of residence (OR = 2.74, 95 % CI [1.11, 6.74)]), and exposure to point-of-sale advertising within the last 30 days (OR = 2.87, 95 % CI [1.26, 6.54]) contributed significantly to a model predicting the likelihood of reporting daily occurrence of smoking/SHS in the home. Conclusions While few women reported having ever used tobacco, one in seven women in this study reported that smoking/SHS occurred daily in their homes. Therefore SHS exposure is a potential health concern for women and children in this rural community. Findings from this study provide baseline data for monitoring tobacco control policies in Ethiopia, particularly in relation to the promotion of smoke-free homes, and could be used to inform prevention program development.